The C-terminal domain of p53 orchestrates the interplay between non-covalent and covalent poly(ADP-ribosyl)ation of p53 by PARP1. Issue 2 (4th December 2017) - Fischbach, Arthur; Krüger, Annika; Hampp, Stephanie; Assmann, Greta; Rank, Lisa; Hufnagel, Matthias; Stöckl, Martin T; Fischer, Jan M.F; Veith, Sebastian; Rossatti, Pascal; Ganz, Magdalena; Ferrando-May, Elisa; et al.
Abstract: The post-translational modification poly(ADP-ribosyl)ation (PARylation) plays key roles in genome maintenance and transcription. Both non-covalent poly(ADP-ribose) binding and covalent PARylation control protein functions, however, it is unknown how the two modes of modification crosstalk mechanistically. Employing the tumor suppressor p53 as a model substrate, this study provides detailed insights into the interplay between non-covalent and covalent PARylation and unravels its functional significance in the regulation of p53. We reveal that the multifunctional C-terminal domain (CTD) of p53 acts as the central hub in the PARylation-dependent regulation of p53. Specifically, p53 bound to auto-PARylated PARP1 via highly specific non–covalent PAR-CTD interaction, which conveyed target specificity for its covalent PARylation by PARP1. Strikingly, fusing the p53-CTD to a protein that is normally not PARylated, renders this a target for covalent PARylation as well. Functional studies revealed that the p53–PAR interaction had substantial implications on molecular and cellular levels. Thus, PAR significantly influenced the complex p53–DNA binding properties and controlled p53 functions, with major implications on the p53-dependent interactome, transcription, and replication-associated recombination. Remarkably, this mechanism potentially also applies to other PARylation targets, since a bioinformatics analysis revealed that CTD-like regions are highly enriched in the PARylated proteome.